Drones and the future of armed conflict : ethical, legal, and strategic implications - Cortright, David, 1946-; Fairhurst, Rachel; Wall, Kristen (Chicago : The University of Chicago Press, 2016)
Presenting a robust conversation among leading scholars in the areas of international legal standards, counterterrorism strategy, humanitarian law, and the ethics of force, this book takes account of current American drone campaigns and the developing legal, ethical, and strategic implications of this new way of warfare.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 27, 2015).
Keywords: Air warfare (International law); Uninhabited combat aerial vehicles; Aeronautics, Military -- Law and legislation -- United States; Military ethics -- United States; Law; United States of America, USA; Military & defence strategy; Weapons & equipment; Jurisprudence & general issues